The Role of Laboratory Diagnostics and Nursing in Public Health Strategies for Malaria Elimination - Rayan Nasser Alzarbah; Adel Mughawi Yahya Asiri; Mousa Mohammed Shami Asir; Mofareh Mohamed Ali Asiri; Mohammad Hussin Qassim Asiri; Mohammed Ibrahim Mohammed Alshahrani; Salim Hassan Mohamed Sahari; Yahya Gobran Ali Sahhari; Abdul Majeed Hussein Mansour Al-Muhaya; Saad Ali Abdullah Safiyah (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Malaria mainly manifests into a highly threatening global health challenge where the different tropical and subtropical regions are endemic to this disease. It is said that nearly 241 million cases were reported of malaria among the total global population in 2020 according to the last report of the World Health Organization (WHO), and it has led to nearly 627,000 deaths. Most of the cases reported above have been from sub-Saharan Africa, where the majority of populations affected are children less than five years and pregnant women. Despite these unfavorable figures, amazing progress has been noted in malaria control and elimination over decades. Nonetheless, global malaria elimination will need an integrated public health approach with laboratory diagnostics and nursing at the forefront. Aim of work: To explore the contributions of laboratory diagnostics and nursing to public health strategies for malaria elimination, emphasizing their roles in diagnosis, treatment, prevention, and community engagement. Methods: We conducted a comprehensive search in the MEDLINE database's electronic literature using the following search terms: Role, Laboratory Diagnostics, Nursing, Public Health Strategies, Malaria Elimination. The search was restricted to publications from 2016 to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion: Diagnosis through laboratory tests and nursing activities is indispensable to the public health strategy of malaria elimination. Gradually, diagnostics will develop evidence-based decisions for screening and targeting specific populations at high risk. Yet, nursing will act as a linking channel between healthcare systems and communities in providing preventive, curative, and diagnostic services that can save lives and reduce disease transmission. To be successful, hence, all the multidimensional challenges to malaria elimination need strong health systems and community engagement in the collaboration of these two practices. Addressing the biomedical and social determinants of health will take public health strategies even closer to the global dream of a malaria-free world.